RURAL HEALTHCARE MANAGEMENT FOR SINDH USING SMART TECHNOLOGIES - Mohsin Ali Shah Syed; Kandeel Fatima; Sarfaraz Khan Turk; Sasuee Khatoon; Hajira Shaikh; Muhammad Aamir Panhwar (Spectrum of Engineering Sciences, 2025)
A poor infrastructure combined with insufficient medical staff and minimal technological resources prevents rural areas in Sindh from obtaining quality healthcare services. A Rural Healthcare Management System (RHMS) uses mobile health units with telemedicine along with a digital data collection platform to respond to these rural healthcare issues. The system establishes its mission to deliver prompt quality healthcare services at reasonable prices to distant communities. RHMS implements community health workers together with smartphones and cloud-based data storage and centralized dashboards and monitoring capabilities for decision-making functions. This paper examines the systematic approach to design and implements the system alongside expected outcomes and challenges with future improvement goals.